2017
DOI: 10.1037/emo0000248
|View full text |Cite
|
Sign up to set email alerts
|

The temporal deployment of emotion regulation strategies during negative emotional episodes.

Abstract: Time is given a central place in theoretical models of emotion regulation (Gross, 1998, 2015), but key questions regarding the role of time remain unanswered. We investigated 2 such unanswered questions. First, we explored when different emotion regulation strategies were used within the course of an emotional episode in daily life. Second, we investigated the association between the temporal deployment of strategies and negative emotional experience. We conducted a daily diary study in which participants (N =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 37 publications
6
72
1
Order By: Relevance
“…Examining the emotion regulation people use to cope with daily political events, therefore, provides a novel real-world context for testing and understanding emotion regulation "in the wild" (Brans et al, 2013;Kalokerinos et al, 2017). Our results coincide with a number of key findings from existing studies.…”
Section: Discussionsupporting
confidence: 83%
“…Examining the emotion regulation people use to cope with daily political events, therefore, provides a novel real-world context for testing and understanding emotion regulation "in the wild" (Brans et al, 2013;Kalokerinos et al, 2017). Our results coincide with a number of key findings from existing studies.…”
Section: Discussionsupporting
confidence: 83%
“…In this case, political action itself could represent emotion regulation as individuals attempt to change the situation itself as a way to change their emotions (e.g., situation modification; Gross, 1998). The present pattern of findings could also be understood from an emotion regulation dynamics perspective, wherein individuals may attempt multiple forms of emotion regulation within a given emotional episode (e.g., Kalokerinos, Résibois, Verduyn, & Kuppens, 2017). If individuals initially attempt reappraisal and are successful in this attempt, there is no need to engage in additional forms of regulation (such as political action, if individuals indeed consider action as a form of regulation).…”
Section: Limitations and Future Directionsmentioning
confidence: 78%
“…It should be noted that there is a burgeoning literature on the contextual factors that influence when and for whom any given emotion regulation strategy is effective in the immediate term (i.e., whether a strategy reduces negative affect immediately after being used; Aldao, 2013;Webb et al, 2012). Researchers have demonstrated that a multitude of factors can influence a given strategy's effectiveness (e.g., situational goals; English et al, 2017; perceived controllability of a stressor; Haines et al, 2016; timing of strategy use; Kalokerinos et al, 2017), which may call into question whether strategies can be reliably distinguished as adaptive or maladaptive. However, researchers studying BPD, and psychopathology more broadly, have consistently found empirical evidence that putatively adaptive and putatively maladaptive strategies can be differentiated based on individual differences (e.g., Aldao & Nolen-Hoeksema, 2012;Naragon-Gainey et al, 2017;Neacsiu et al, 2010;Southward & Cheavens, 2020) and within-person patterns of use (e.g., McMahon & Naragon-Gainey, 2019).…”
Section: Behavioral Responses To Emotions In Bpdmentioning
confidence: 99%